Quality of Healthcare in Acute Pediatric Care Unit in a Tertiary Hospital in Tanzania: A Case of Muhimbili National Hospital - Remtullah, Aleya Z.; Sirili, Nathanael; Anaeli, Amani; Massawe, Augustine; Manji, Karim; Sunguya, Bruno F. (Frontiers in Pediatrics, 2020)
ABSTRACT Background Quality of care in a critical care unit is vital for the outcomes of critically ill people and especially children, who are more at risk. Although evidence is mixed, only a handful remains documented about the role of quality of care among children in the context of tertiary hospitals of low-income countries such as Tanzania. This study therefore assessed the quality of healthcare in Acute Paediatric Care Unit (APCU) at Muhimbili National Hospital in Tanzania over three months. Methodology: This mixed method cross sectional study employed both qualitative and quantitative approaches to gather data from 107 participants that included caregivers of children admitted, and healthcare providers in APCU at MNH. Components of the Donabedian model were used to assess quality of care. Descriptive analyses was conducted for quantitative data while thematic analyses was conducted for qualitative data. Results: A total of 24(26.7%) of the children admitted in APCU died in the three-month period of data collection. Of them, 41.7% died during the first 24 hours of admission. The median duration of APCU admission was five days. Despite the noted challenges, most of the caregivers were very satisfied 34(37.8%) or satisfied 22(24.4%) with the quality of services provided. The physical setting in APCU had the basic requirements for management of critically ill children but was insufficient in infrastructure; healthcare providers trained in critical care and updated treatment guidelines amongst others. We noted inadequacy in on-job training of health workers, feedback process and obvious delays in the referral system. Conclusions and Recommendations Although one in four children admitted in the APCU at MNH died, the overall quality of care in this tertiary referral hospital was modest as it achieved the minimum acceptable standards. To enhance quality of care, it is vital to improve infrastructure, update treatment guidelines, train staff in critical care and improve the feedback process especially during emergencies and deaths.